2022
DOI: 10.3389/fpubh.2022.875727
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practices Toward Coronavirus Disease (COVID- 19) in Southeast and South Asia: A Mixed Study Design Approach

Abstract: BackgroundCoronavirus has spread to almost every country since its emergence in Wuhan, China and countries have been adopted an array of measures to control the rapid spread of the epidemic. Here, we aimed to assess the person's knowledge, attitude and practices (KAP) toward the COVID-19 epidemic in Southeast and South Asia applying the mixed study design (cross-sectional and systematic review).MethodsIn the cross-sectional study, 743 respondents' socio-demographic and KAP-related information was collected thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 66 publications
(100 reference statements)
3
11
0
1
Order By: Relevance
“…Males had a significantly higher level of good knowledge about COVID-19 than females. Findings of the study is supported by the findings of the studies conducted in Southeast and South Asian countries and Bangladesh [14], [37], [45]. This might be due to the fact that males were more concerned about the disease and its preventive mechanisms.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Males had a significantly higher level of good knowledge about COVID-19 than females. Findings of the study is supported by the findings of the studies conducted in Southeast and South Asian countries and Bangladesh [14], [37], [45]. This might be due to the fact that males were more concerned about the disease and its preventive mechanisms.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, the success of all these efforts taken by the Government in containing the rapid spread of COVID-19 largely depends on acceptance of people and adopting the control measures that depends on the perception, knowledge, and attitude of people toward COVID-19. Recent studies of Southeast and South Asian countries found that effectiveness of the preventive measures for COVID-19 largely depends on the cooperation and compliance of the people [14].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the COVID-19 pandemic, medical students feel more confused about their future careers, which can lead to poor mental health problems such as fear and insomnia [ 13 ]. The main COVID-19 control practices include wearing masks, hand washing, avoiding crowded places, and social distance [ 14 ]. Studies have shown that social distancing was necessary to effectively control the COVID-19 pandemic, it also has a severe negative impact on college students' sleep quality and sleep behavior alongside a consensus on the literature [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic caused by the SARS-CoV-2 virus has emerged as a global public health emergency, with millions of reported cases and fatalities worldwide [1][2][3][4][5][6][7]. Chronic kidney disease (CKD) is a common comorbidity among COVID-19 patients, which is associated with increased morbidity and mortality [8][9][10].…”
Section: Introductionmentioning
confidence: 99%